Possible Influence of Natural Events on Heavy Metals Exposure from Shellfish Consumption: A Case Study in the North-East of Italy - Losasso, Carmen; Bille, Laura; Patuzzi, Ilaria; Lorenzetto, Monica; Binato, Giovanni; Dalla Pozza, Manuela; Ferrè, Nicola; Ricci, Antonia (Frontiers in Public Health, 2015)
The objective of this study was the estimation of the exposure over time to heavy metals (cadmium, mercury and lead) due to shellfish consumption in the Veneto Region, Italy. Shellfish consumption was investigated by a food frequency consumption survey. Altogether, 1949 households, stratified into the five most populated areas of the Veneto Region, were involved in the study. Exposure estimation to heavy metals was carried out taking into account the level of metal measured in samples of Manila clams (Ruditapes philippinarum) and grooved carpetshell (Ruditapes decussatus), collected in the frame of the monitoring activities of mollusk production areas of Veneto Region, between January 2007 and December 2012. A general high contribution of the considered shellfish to the Tolerable Weekly Intake (TWI) was noticed in the case of cadmium, especially in 2011, when a considerable increase in cadmium intake was estimated. This was probably due to a heavy rainfall event that triggered catastrophic flooding with high impact on shellfish capture areas in November 2010. The results strongly emphasise the importance of dealing with food safety in a holistic way, taking into account the potential impact of extraordinary natural events on food chain contamination, in order to identify food hazards at an early stage, before developing into a real risk for consumers.